Aggression is not blind: dominance and social history modulate murine responses to social instigation. - Nagai, Tomoya; Takahashi, Aki (Psychopharmacology, 2026)
Rationale: The social instigation procedure is a behavioral model used to induce escalated aggression in male mice. In this procedure, a brief indirect encounter with a novel rival male (instigator) placed in a tube enhances aggression toward an intruder in the subsequent agonistic encounter. However, social factors that drive this pro-aggressive effect remain unclear. Objectives: This study investigates how social novelty, familiarity, and dominant-subordinate hierarchy influence the pro-aggressive effect of social instigation. Methods: A male instigator in a perforated tube was placed in the test mouse's home cage for 5 min, followed by the introduction of an intruder male to assess the test animal's aggression. Different types of instigators were used to examine the roles of social novelty and dominance hierarchy. Aggressive behavior was compared to baseline aggression without social instigation. Results: Exposure to a novel male instigator escalated aggression, as indicated by shorter attack latency and increased frequency and duration of aggressive behaviors. In contrast, when a familiar intruder male was presented as the instigator, attack latency was reduced but the total amount of aggressive behaviors remained unchanged. When the instigator had an established dominant-subordinate relationship with the test mouse, aggressive behavior was not enhanced. However, when a familiar male without a prior dominant-subordinate relationship was used, aggressive behavior increased to levels comparable to those induced by a novel instigator. Conclusions: Social novelty and an ambiguous social hierarchy of the instigator promote the pro-aggressive effect of social instigation in male mice.